Bihar Third Five Year Plan Volume I - Planning Commission (Planning Commission, 1961)
The inadequacy of irrigation facilities throws into bold relief the dependence of the agricultural sector on the monsoon. the result has been that agricultural production has always suffered violent fluctuations and depended upon the adequate distribution or otherwise of the rainfall. the main crop in the State is winter paddy and this crop not merely requires rainfall in adequate quantity but also demands that the rainfall should be distributed over the season of the crop. When rainfall is heavy, there is also the onslaught of floods, specially in North Bihar, and this serves as a further deterring influence against improvement in the agricultural sector. Floods and drought have contributed mostly to the stagnation of the agricultural sector and also to distress migration from the State over the years.
Bihar